Hubungn antara Jenis Pekerjaan, Masa Kerja dan Pola Kerja Terhadap Risiko Penyakit Jantung Koroner pada Tenaga Kesehatan Rumah Sakit Islam Jakarta Pondok Kopi - Emilya, Vita; Wening Tri Mawanti; Atik Mufidah (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2025)
Coronary heart disease is often found in workers, including hospital health workers. The purpose of the study was to determine the relationship between the type of work, working period and work pattern on the risk of coronary heart disease in health workers at the Jakarta Islamic Hospital Pondok Kopi. This study is an analytical research with a cross sectional method. Samples were obtained by taking primary data from questionnaires and secondary data from medical check-up results. A total of 70 people met the inclusion criteria as a sample. The risk of cardiovascular disease is calculated using the Framingham score online. Based on the results of the analysis using SPSS 21.0, the relationship between the working period and the risk of CHD was obtained with a value of p=0.029 (p<0.05). Meanwhile, the type of work and work pattern were not found to be associated with the risk of Coronary Heart Disease (p=0.361 and p=0.735). Penyakit jantung koroner sering dijumpai pada pekerja antara lain tenaga kesehatan rumah sakit. Tujuan penelitian untuk mengetahui hubungan antara jenis pekerjaan, masa kerja dan pola kerja terhadap risiko penyakit jantung koroner pada tenaga kesehatan Rumah Sakit Islam Jakarta Pondok Kopi. Penelitian ini merupakan penelitian analitik dengan metode cross sectional. Sampel diperoleh dengan pengambilan data primer kuesioner dan data sekunder dari dokumen hasil medical check up. Sebanyak 70 orang memenuhi kriteria inklusi sebagai sampel. Risiko penyakit cardiovaskuler dihitung menggunakan skor Framingham secara online. Berdasarkan hasil analisis menggunakan SPSS 21.0 didapatkan hubungan antara masa kerja dengan risiko PJK dengan nilai p=0,029 (p<0,05). Sedangkan jenis pekerjaan dan pola kerja tidak didapatkan hubungan dengan risiko Penyakit Jantung Koroner (nilai p=0,361 dan p=0,735).